Experiencing the worlds religions / professional education : assessment. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2013)
This LET Reviewer is prepared to help you pass the LET. It will help in comprehensive and focused it covers all the competencies for the tests in professional education-assessment as contained in the table of specifications (TOS) for the LET, it helps with the quality test items, simulation for shading of answer sheet and it has additional references to ensure the mastery of LET competencies.
4.1. Apply principles in constructing traditional and alternative/authentic forms of high quality assessment -- 4.2. Interpret assessment results -- 4.3. Utilize processed data and assessment results in reporting learners' performance to improve teaching and learning -- 4.4. Demonstrate skills in the use of techniques and tools in assessing affective learning -- 4.5. Assign students' marks/ratings.
Keywords: LET -- EXAMINATION -- ASSESSMENT